Facial emotion processing hemispheric bias is weakly associated with handedness, autistic traits and biological sex, but not age - B. E. Speranza; M. Do; A. T. Hill; P. H. Donaldson; P. G. Enticott; M. Kirkovski (BMC Psychology)
Abstract Background Right-hemisphere brain regions are strongly implicated in facial emotion processing (FEP), a phenomenon termed right-hemispheric bias. Variability in FEP hemispheric bias is thought to underpin differences in facial emotion recognition ability and has been associated with age, handedness, biological sex, and autistic traits. However, findings from research to date investigating factors associated with FEP hemispheric bias have been inconsistent. Objective To examine if FEP hemispheric bias can be predicted by individual factors such as age, biological sex, handedness, and autistic traits. Methods 427 adults recruited from the general population aged 18–67 years completed the Autism-spectrum Quotient. We also assessed covariates previously linked with FEP hemispheric bias including age, handedness, and biological sex. FEP hemispheric bias was indexed using laterality quotients calculated from a Chimeric Faces Task, where participants indicated which of two identical (but mirrored) half-emotional half-neutral (no emotion) chimeric faces were more emotive. Results Linear regression models revealed that (1) handedness predicted FEP hemispheric choice bias, (2) the attention switching Autism-spectrum Quotient subscale predicted FEP hemispheric reaction time bias, and (3) the imagination Autism-spectrum Quotient subscale predicted FEP hemispheric reaction time bias for males, but not females. Conclusions These findings indicate that the relationship between autistic traits and FEP hemispheric bias is nuanced. Additionally, handedness influences hemispheric bias effects during FEP. Future research should endeavour to investigate if FEP hemispheric bias is dependent on the emotion being observed and consider using more direct measures of hemispheric bias.